First Molecular Evidence for Mycoplasma haemocanis and Candidatus Mycoplasma haematoparvum in Asymptomatic Shelter Dogs in Kyrgyzstan - Altay, Kursat; Aydin, Mehmet Fatih; Aytmirzakizi, Ayperi; Jumakanova, Zarima; Cunusova, Ayday; Dumanli, Nazir (Kafkas Univ, Veteriner Fakultesi Dergisi, 2020)
Mycoplasma haemocanis (Mhc) and Candidatus Mycoplasma haematoparvum (CMhp) have been investigated using species specific PCR and sequencing in 170 dogs from Kyrgyzstan. Maximum likelihood estimation (MLE) of the infection rates with 95% confidence intervals (CI) was calculated. The molecular prevalence of hemoplasma infection was 5.29% (CI 2.57-9.34). It was found that, five (2.94%, CI 1.06-6.22) samples were found to be infected with Mhc, one (0.59%, CI 0.03-2.57) sample with CMhp and three (1.76%, CI 0.44-4.52) samples with both species. These results demonstrate that dogs can be exposed to each haemoplasma species and provide first molecular evidence for these species in Kyrgyzstan.
Kırgızistan’da asemptomatik barınak köpeklerinde mycoplasma haemocanis ve candidatus mycoplasma haematoparvum için ilk moleküler kanıt
Keywords: Canine; Haemoplasmas; PCR; Kyrgyzstan